Peran Kepemimpinan Kemuhammadiyahan dalam Membangun Karakter Siswa di MTS Muhammadiyah 2 - Della Elwis Putri; Sintia Larasati; Rini Imelia Putri; Anggi Nirwana; Rifa Aprilia Putri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the role of Muhammadiyah leadership in building student character at MTs 2 Muhammadiyah. The method used in this study is a qualitative approach, with data collection through interviews, observations, and documentation studies. The results of the study indicate that Muhammadiyah leadership has a significant positive impact on the formation of student character, including in moral, ethical, and social aspects. Leaders in the MTs 2 Muhammadiyah environment apply religious and social values upheld by Muhammadiyah, which encourage students to behave well and responsibly. The conclusion of this study confirms that leadership based on Muhammadiyah values not only improves academic achievement, but also shapes students' character into better individuals, who are ready to face challenges in the future.